People management skills in practice : a case study collection - Levesque, Laurie L. (Routledge, 2025)
"This practical text covers the essential aspects of managing employees, providing relevant and interesting case studies to enable students to develop the management skills and approaches needed at all levels. The book includes a wealth of case studies across industries including public relations, gaming, food service, healthcare, and nonprofits and hailing from several regions and cultures (including Australia, the Philippines, US, and Taiwan). The five core sections of the text each focus on a specific managerial skillset: dilemmas managers face when creating a positive work culture, power and influencing others, conflict within a team, managing a cross-cultural team, and motivating and fostering employee engagement. Within each section, short case studies feature real-life situations and managers who had to assess and respond to various challenges with subordinates, colleagues, or their immediate boss. Each case is supported by a case synopsis, reflective questions, and related learning activities. Instructors have access to teaching notes for each case that provide detailed discussion questions, an overview of concepts and their academic references, advanced reading suggestions, and activities that can be employed in class or as supplemental learning assignments. Comprehensive and practical, this case textbook is perfect core reading for any postgraduate managerial skills course, MBA, professional qualifications in management and leadership, and degree apprenticeship programmes"-- Provided by publisher.
Keywords: Personnel management -- Case studies.; elektronické knihy; electronic books